Sharia Business Model Bumnagari with BMC Models Approach (Decree of Bumnagari Magek Sakabek, Agam Regency) - Dewi, Yenty Astarie; Gusvi, Fitrina; Satria, Wahyu (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
This research aims to design a Sharia business model for BUMNagari Magek Sakabek. The type of business conducted by BUMNagari Magek Sakabek involves a savings and loan business unit. The method used is Qualitative Research with data analysis techniques using the Business Model Canvas (BMC Models), which analyzes the nine Canvas elements into the Sharia Business Concept, namely customer segments, value propositions, channels, customer relationships, revenue streams, key resources, key activities, key partnerships, and cost structure. Each BMC element must depict and explain how Sharia principles are applied in business transactions. From the discussion results, each BMC element is analyzed to create a Sharia business model that can be implemented by the savings and loan business unit of BUMNagari Magek Sakabek, one that is sustainable and competitive in the long term, while also providing positive value to the community related to Sharia business. From the research findings, it can be concluded that the business model designed with BMC shows that 8 BMC elements have undergone corrections or changes in applying Sharia principles, which are value propositions, channels, customer relationships, revenue streams, key resources, key activities, key partnerships, and cost structure. Therefore, the Sharia business model can be implemented in the Savings and Loan Business Unit of BUMNagari Magek Sakabek.Penelitian ini bertujuan untuk merancang model bisnis syariah pada Badan Usaha Milik Nagari (BUMNag) Magek Sakabek. BUMNag Magek Metode yang digunakan untuk merancang model bisnis syariah pada Unit Bisnis Simpan Pinjam BUMNag Magek Sakabek adalah dengan pendekatan Business Model Canvas (BMC) . Business Model Canvas terdiri dari sembilan elemen yaitu customer segements, value propositions, channels, customer relationships, revenue streams, key resources, key activities, key partnership dan costructure. Setiap elemen BMC harus menggambarkan dan menjelaskan bagaimana prinsip syariah diterapkan dalam transaksi bisnis. Dari hasil evaluasi masing-masing elemen BMC dianalisis sehingga tercipta model bisnisÂ syariah yang dapat diimplementasikan unit bisnis simpan pinjam BUMNag Magek Sakabek yang sustainable dan bersaing dalam jangka panjang sekaligus memberikan nilai positif bagi masyarakat terkait bisnis syariah.Dari hasil penelitian dapat disimpulkan bahwa model bisnis yang dirancang dengan BMC menunjukkan terdapat 8 elemen BMC yang mengalami koreksi atau perubahan dalam menerapkan prinsip syariah yaitu value propositions, channels, customer relationships, revenue streams, key resources, key activities, key partnership dan costructure. Sehingga model bisnis syariah dapat diimplementasikan pada unit Bisnis Simpan Pinjam BUMNag Magek Sakabek.